Analisis Cash Waqf Linked Deposit (CWLD) Perspektif Empat Mazhab - Zulfa, Ainiyatuz; Ahmad Fauzan Mubarok; Nafisah, Zahrotun (Universitas Islam Lamongan, 2024)
Cash waqf in Indonesia has great potential to improve community welfare. However, the realization is still not optimal. After previously OJK developed a cash waqf product integrated with sukuk (CWLS). Now OJK is reissuing a cash waqf product in collaboration with a deposit product or called cash waqf linked deposit (CWLD), as a deposit-based waqf innovation, offering a solution by integrating the social and commercial functions of sharia banking. However, there are no regulations governing cash waqf linked deposit (CWLD) itself, the implementation of CWLD can be different depending on the Islamic law adopted. In Islam there are four main schools of thought, each of which has a view on the concept of cash waqf and investment. Therefore, there is a need for studies related to CWLD analysis from an Islamic legal perspective. The research method used is library research. The source of data obtained is primary data sourced from books, journals, legal articles and other research results. The data collection technique in this research is by collecting literature that is relevant to this research. The results of the research obtained are that there is difference of opinion from four mazhab of thought regarding cash waqf linked deposit (CWLD). The Hanafi Mazhab and Maliki Mazhab allow it, while the Syafi’i Mazhab and Hanbali Mazhab do not allow cash waqf linked deposit (CWLD)